The importance of contemporary fiqh in Islamic banking and finance - Mohd Asri, Aisyatul Umairah; Mohd Anuar, Nurul Auni Athirah (2025)
Islamic law continues to evolve through the lens of contemporary fiqh, a discipline that responds to the modern realities of Islamic banking and finance. This study aims to understand the basic concepts of contemporary fiqh, to explain its importance in resolving current financial issues from a Sharia-compliant perspective, and to explore real-world Islamic financial products guided by Sharia advisory institutions. These institutions play a crucial role in ensuring that financial instruments remain aligned with Islamic ethical principles while addressing new economic developments. Using a qualitative research approach through library-based research, this research relies on secondary data including academic theses, journals, and digital sources. The findings underscore that contemporary fiqh is not simply a reinterpretation of classical legal thought, but an advancement needed to ensure that Islamic finance remains relevant in addressing the complexities of the modern economy. Through the process of ijtihad, contemporary scholars are able to construct solutions to today’s financial challenges without compromising the core values of Sharia. By analyzing how products such as sukuk, Islamic insurance (takaful), and Islamic investment contracts are shaped, this research reveals the dynamic application of fiqh in real-world settings. It also highlights the challenges faced in maintaining both innovation and compliance. Ultimately, the study asserts that contemporary fiqh plays a crucial role in bridging the timeless principles of Islamic law with the demands of the fast-paced financial world—offering ethical, moral, and practical guidance rooted in the objectives of Sharia.